Efficacy and safety of long-acting injectable oral antipsychotics in the treatment of patients with early-phase schizophrenia-spectrum disorders: a systematic review and meta-analysis - Giovanni Vita; Angelantonio Tavella; Giovanni Ostuzzi; Federico Tedeschi; Michele De Prisco; Rafael Segarra; Marco Solmi; Corrado Barbui; Christoph U. Correll (SAGE Publishing, 2024)
Background: Long-acting injectable antipsychotics (LAIs) have advantages over oral antipsychotics (OAPs) in preventing relapse and hospitalization in chronically ill patients with schizophrenia-spectrum disorders (SSDs), but evidence in patients with first-episode/recent-onset, that is, early-phase-SSDs is less clear. Objectives: To assess the relative medium- and long-term efficacy and safety of LAIs versus OAPs in the maintenance treatment of patients with early-phase SSDs. Method: We searched major electronic databases for head-to-head randomized controlled trials (RCTs) comparing LAIs and OAPs for the maintenance treatment of patients with early-phase-SSDs. Design: Pairwise, random-effects meta-analysis. Relapse/hospitalization and acceptability (all-cause discontinuation) measured at study-endpoint were co-primary outcomes, calculating risk ratios (RRs) with their 95% confidence intervals (CIs). Subgroup analyses sought to identify factors moderating differences in efficacy or acceptability between LAIs and OAPs. Results: Across 11 head-to-head RCTs ( n  = 2374, median age = 25.2 years, males = 68.4%, median illness duration = 45.8 weeks) lasting 13-104 (median = 78) weeks, no significant differences emerged between LAIs and OAPs for relapse/hospitalization prevention (RR = 0.79, 95%CI = 0.58-1.06, p  = 0.13) and acceptability (RR = 0.92, 95%CI = 0.80-1.05, p  = 0.20). The included trials were highly heterogeneous regarding methodology and patient populations. LAIs outperformed OAPs in preventing relapse/hospitalization in studies with stable patients (RR = 0.65, 95%CI = 0.45-0.92), pragmatic design (RR = 0.67, 95%CI = 0.54-0.82), and strict intent-to-treat approach (RR = 0.64, 95%CI = 0.52-0.80). Furthermore, LAIs were associated with better acceptability in studies with schizophrenia patients only (RR = 0.87, 95%CI = 0.79-0.95), longer illness duration (RR = 0.88, 95%CI = 0.80-0.97), unstable patients (RR = 0.89, 95%CI = 0.81-0.99) and allowed OAP supplementation of LAIs (RR = 0.90, 95%CI = 0.81-0.99). Conclusion: LAIs and OAPs did not differ significantly regarding relapse prevention/hospitalization and acceptability. However, in nine subgroup analyses, LAIs were superior to OAPs in patients with EP-SSDs with indicators of higher quality and/or pragmatic design regarding relapse/hospitalization prevention (four subgroup analyses) and/or reduced all-cause discontinuation (five subgroup analyses), without any instance of OAP superiority versus LAIs. More high-quality pragmatic trials comparing LAIs with OAPs in EP-SSDs are needed. Trial registration: CRD42023407120 (PROSPERO).